The Activities of Heparan Sulfate and its Analogue Heparin are Dictated by Biosynthesis, Sequence, and Conformation - Skidmore, Mark A.; Guimond, Scott E.; Rudd, Tim R.; Fernig, David G.; Turnbull, Jeremy E.; Yates, Edwin A. (Connective Tissue Research, 2008)
The glycosaminoglycan heparan sulfate (HS), is expressed on the surface of virtually all mammalian cells and is implicated in many crucial biological activities. The activities of HS and its close structural analogue heparin are mediated through interactions with proteins. However, the relationship between structure and activity is not simple, because the structure and conformation of HS and heparin are complex. This review surveys some of the relevant findings in HS/heparin chemistry, biochemistry, and biology.